Principles of quantitative chemical analysis - Levie, Robert de (New York : McGraw-Hill, 1997)
Chemistry and Physics
Keywords: Chemical analysis; Quantitative chemistry; Complexation; Chromatography; Electrochemical equilibra; Voltammetry; Light; Optics; Radiochemistry